Morphology of Peeled Internal Limiting Membrane in Macular Hole Surgery - Mun Y. Faria; David C. Sousa; Bruna C. Almeida; Andreia L. Pinto; Nuno P. Ferreira (Journal of Ophthalmology)
Purpose. The aim of this work was to describe the ultrastructure and behavior of peeled internal limiting membrane (ILM) in macular hole (MH) surgery. Methods. Seven patients with MH were included, and vitrectomy with ILM peeling was performed in all patients. The ILM inverted flap technique was used. Two other flaps of ILM of the same patient were collected and studied using light and transmission electron microscopy (TEM). ILM cell type, distribution, and morphology were analyzed, and the proliferation or fusion potential of the ILM interface was evaluated. Results. ILM vitreous sides in apposition showed signs of proliferative fibrotic activity, producing a basal membrane that merges ILM sides. Conclusions. Epiretinal cells in ILM show proliferative capacity, with formation of microfibrils between adjacent sides of the ILM, which may explain adherence of ILM flaps to the hole border, contributing to closure of the hole in MH surgery. This trail is registered with NCT03799575.